2021
DOI: 10.14744/bej.2021.17894
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central corneal thickness measurements of five different devices with ultrasound pachymetry in healthy eyes

Abstract: Objectives: Several methods of measuring central corneal thickness (CCT) have been compared, however, the data are still limited and conflicting. The aim of this study was to determine the agreement of CCT measurements performed in healthy eyes using ultrasound pachymetry (USP), non-contact tono/pachymetry, specular microscopy, biometry, Scheimpflug-based corneal topography, and optical coherence tomography (OCT). Methods: All of the participants underwent a complete ophthalmological examination. The CCT of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is important to determine the discrepancies between devices. 10 A previous study showed that CCT measurements in healthy individuals using ultrasonic pachymetry and optical instruments are not directly interchangeable. 7 Another study by Omoto et al revealed moderate agreement in CCT measurement between two optical biometers using SS-OCT. 11 This study aims to compare the agreement between SS-OCT and the Scheimp ug camera in CCT measurement in patients with high myopia.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to determine the discrepancies between devices. 10 A previous study showed that CCT measurements in healthy individuals using ultrasonic pachymetry and optical instruments are not directly interchangeable. 7 Another study by Omoto et al revealed moderate agreement in CCT measurement between two optical biometers using SS-OCT. 11 This study aims to compare the agreement between SS-OCT and the Scheimp ug camera in CCT measurement in patients with high myopia.…”
Section: Introductionmentioning
confidence: 99%